Antropologia medica applicata at home: Dalle criticità alla necessità di un posizionamento “eretico” - Spada, Stefania (Antropologia Pubblica, 2024)
This contribution aims to reflect on personal tensions emerged from an action-research carried out within a public hospital’s gynecology unit located in north western Italy. I got involved on this fieldwork in two different ways: both as a Ph.D. researcher, willing to investigate the capability of informed consent to protect or not migrant patients’ right to health, and as an anthropologist-tutor having a specific educative responsibility - identifying critical situations in the relations between health care professionals and migrant patients in order to develop more equal relationships of care. More specifically I analyze the relationship among three ethically relevant topics such as: doing research "at home", the dialogue between subjectivity and experience and the challenging concretization of an appropriate methodology in anthropology. Starting from the ethical dilemmas emerged in fieldwork I want to reflect on the political dimensions of being and researching "at home", on anthropology's public role and on the lack of recognition of the practitioner anthropologist and his/her work's legitimacy in this field.